2020
DOI: 10.1186/s12576-020-00774-x
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological investigation of the contribution of attention to altered pain inhibition processes in patients with irritable bowel syndrome

Abstract: Irritable bowel syndrome (IBS) is a functional gastrointestinal disorder associated with chronic abdominal pain and altered pain processing. The aim of this study was to examine whether attentional processes contribute to altered pain inhibition processes in patients with IBS. Nine female patients with IBS and nine age-/sex-matched controls were included in a pain inhibition paradigm using counter-stimulation and distraction with electroencephalography. Patients with IBS showed no inhibition of pain-related br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 96 publications
0
9
0
Order By: Relevance
“…A source localization of power change was performed to estimate the cortical sources associated with pain relief (see Refs. 58 and 59 for a source estimation pipeline). The power decomposition on the source from 4 to 7 Hz was computed using Welch method.…”
Section: Methodsmentioning
confidence: 99%
“…A source localization of power change was performed to estimate the cortical sources associated with pain relief (see Refs. 58 and 59 for a source estimation pipeline). The power decomposition on the source from 4 to 7 Hz was computed using Welch method.…”
Section: Methodsmentioning
confidence: 99%
“…The total number of participants evaluated in the reviewed studies is 255,068, these being 18 participants from the smallest sample (Rustamov et al, 2020 ) and 161,490 participants from the largest (Chen et al, 2016 ). The proportion of female (51%) and male (49%) participants is balanced, and the mean age is 40.5 years (SD = 7.9), with a range between 18 and 85 years of age.…”
Section: Resultsmentioning
confidence: 99%
“…Lam et al (2019) and Wong et al (2019b) state that one of the principal explanations for the demonstrated biases in the attention network is the presence of chronic thoracic, abdominal and/or pelvic pain, anxiety related to the symptoms, hypervigilance of the pain and visceral hypersensitivity. Along the same lines, another possible explanation for the attention bias is the proposal made by Rustamov et al (2020), which suggests that persons with chronic pain direct a great part of their attention resources to information related to the pain due to their inability to inhibit it.…”
Section: Discussionmentioning
confidence: 99%
“…A Morlet wavelet convolution was computed using the channel time–frequency option. 81 , 82 Thirty-five linearly spaced frequencies were computed between 65 and 100 Hz. For each patient, time–frequency data were averaged across all epochs per condition.…”
Section: Methodsmentioning
confidence: 99%